PBL with the brainstorming method: Can it influence students' critical and creative thinking ability? - Indah Praminingsih; Mieke Miarsyah; Tri Handayani Kurniati (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
The ability to think critically and creatively is a capability that must be possessed by student in this century. This ability is needed to adjust to changes, it takes habit in bringing up new ideas to solve various problems that occur. This study aims to determine the effect of the Problem-Based Learning (PBL) model with the brainstorming method on students' critical and creative thinking abilities. The research method uses quasi-experimental research with a non-equivalent pretest-post-test control group design. The population of this study was class X MIPA students at SMA Negeri 1 Kota Tangerang Selatan for the 2022/2023 academic year. Sampling using a simple random sampling technique, and obtained as many as 80 students. Data on critical and creative thinking ability were obtained through essay tests. Data were analyzed using the MANOVA test. Prerequisite test results obtained data normally distributed and homogeneous. Based on the results of the MANOVA hypothesis test (p <0.05), shows that the treatment of PBL with the brainstorming method influences critical and creative thinking ability with a significance value of 0.000 and 0.008, respectively. The PBL model with the brainstorming method can be used by teachers to improve student's critical and creative thinking ability.